DAMPAK LATIHAN BOX JUMP DENGAN TUCK JUMP TERHADAP POWER TUNGKAI - Ikhwan Khalid; Hendra Rustiawan (Wahana Pendidikan, 2020)
ABSTRACTThe Purpose of this research was to know the impact of box jump exercises with tuck jump against increased power limbs. The use of research methods was pre experimental design. The research design used was two group pretest-posttest design. The population were a joined in extracurricular of 3 High School Bolavoli, Ciamis, Indonesia. The totaling were 26 participants. Sampling techniques used a total sampling. The Instrument used was Sergeant Jump Test. Data analysis used the paired sample T-Test and Independent sample T-Test , the results of the studied were as follows: 1. There was a significant influence of box jump exercises against the enhancement of power limbs with a probability value (sig.) 0.000 < 0.05, 2. There was a significant influence of Tuck jump exercises against increased power limbs with probability value (sig.) 0.000 < 0.05, the conclusion was a box jump exercise was better compared to the tuck jump Exercises for the development of power limbs on volleyball players and the results of this study are expected to be one of the power leg Exercise program recommendations.Keywords: Jump, Plyometric, PowerABSTRAKTujuan penelitian ini untuk mengetahui dampak latihan box jump dengan tuck jump terhadap peningkatan power tungkai. Metode penelitian yang digunakan adalah pre experimental design. Desain penelitian yang digunakan adalah two group pretest-posttest design. Populasinya adalah tim bola voli SMA Negeri 3 Kabupaten Ciamis yang berjumlah 26 orang. Teknik pengambilan sampel menggunakan total sampling. Instrument yang digunakan adalah sergeant jump test. Analisis data menggunakan paired sample t test dan independent sample t-test, hasil penelitian adalah sebagai berikut: 1.Terdapat pengaruh yang signifikan latihan box jump terhadap peningkatan power tungkai dengan nilai probabilitas (sig.) 0.000 < 0.05, 2.Terdapat pengaruh yang signifikan latihan tuck jump terhadap peningkatan power tungkai dengan nilai probabilitas (sig.) 0.000 < 0.05, Kesimpulannya adalah latihan box jump lebih baik dibandingkan dengan latihan tuck jump untuk pengembangan power tungkai pada pemain bola voli dan hasil penelitin ini diharapkan menjadi salah satu rekomendasi program latihan power tungkai.Kata Kunci: Jump, Pliometrik, power